Inhibition of Tumor Cellular Proteasome Activity by Triptolide Extracted from the Chinese Medicinal Plant ‘Thunder God Vine’ - LU, LI (2011)
AIMS: The molecular mechanisms of triptolide responsible for its antitumor properties are not yet fully understood. The ubiquitin/proteasome system is an important pathway of protein degradation in cells. This study investigated whether triptolide may inhibit proteasomal activity and induce apoptosis in human cancer cells. MATERIALS AND METHODS: In vitro proteasome inhibition was measured by incubation of a purified 20S proteasome with triptolide. Human breast and prostate cancer cell lines were also treated with different doses of triptolide for different times, followed by measurement of proteasome inhibition (levels of the chymotrypsin-like activity, ubiquitinated proteins and three well-known proteasome target proteins, p27, IκB-α and Bax) and apoptosis induction (caspase-3 activity and PARP cleavage). RESULTS: Triptolide did not inhibit the chymotrypsin-like activity of purified 20S proteasome. However, treatment of triptolide was able to cause decreased levels of cellular proteasomal chymotrypsin-like activity and accumulation of ubiquitinated proteins and three well-known proteasome target proteins in human breast and prostate cancer cells, associated with apoptosis induction. CONCLUSION: It is possible that at least one of metabolites of triptolide has proteasome-inhibitory activity.